Epigallocatechin gallate, the primary bioactive component from Camellia sinensis: A review on immunomodulatory effects in autoimmune diseases by balancing the differentiation of Th and Treg cells - Vigha Ilmanafi Arifka; Andayana Puspitasari Gani; Retno Murwanti (Shahrekord University of Medical Sciences, 2024)
Autoimmune disease is a chronic condition that requires treatment with prolonged use of drugs. Consequently, there is a significant occurrence of adverse effects and toxicity associated with the medicine. On the other hand, epigallocatechin gallate (EGCG), the primary bioactive catechin in green tea (Camellia sinensis), has been demonstrated to possess anti-inflammatory properties and exhibit therapeutic effects in autoimmune disorders. Therefore, EGCG can be considered a complementary and alternative medicine to address the limitations of current treatment. Turning to the disease pathology, the balance between helper T-cell (Th) and regulatory T-cell (Treg) differentiation is the crucial aspect that needs to be regulated in order to attain immunological tolerance and suppress the incidence and severity of autoimmune disease. Here, we aim to comprehensively review the immunomodulatory effect of EGCG on the balance of Th/Treg cell differentiation in diverse autoimmune disorders. Scientific databases, including Scopus, PubMed, Science Direct, and Google Scholar, were searched using the keywords autoimmune AND (epigallocatechin-3-gallate OR epigallocatechin gallate OR EGCG) AND (Thelper OR Th OR Treg OR CD4). Our review revealed that EGCG has ability to repair the imbalance of Th/Treg cell differentiation in rheumatoid arthritis (RA), multiple sclerosis (MS), ulcerative colitis (UC), and autoimmune uveitis (AU) by inhibiting the differentiation of Th1 and Th17 cells while promoting the differentiation of Th2 and Treg cells, as well as improving the clinical conditions of the tested animals. Hence, it might be inferred that EGCG exhibits considerable promise as a viable complementary and alternative therapeutic option for autoimmune disease.